Investigação da doença aterosclerótica em pacientes transplantados renais e na lista de espera em acompanhamento ambulatorial - Campagnolo, Ângela Quatrin (2013)
Kidney transplantation is the treatment of choice for patients with chronic kidney disease, bringing survival and quality of life over dialysis. Mortality associated with renal transplantation increase in the proportion of deaths related to cardiovascular diseases, which are the main manifestations of atherosclerotic disease. The aim of this study is to evaluate the prevalence of carotid atherosclerosis in patients on the waiting list for renal transplantation and transplant already in attendance at the University Hospital of Santa Maria through ultrasound of carotid arteries and correlate their presence with the Framingham score. We conducted a cross sectional study of 59 prospective kidney transplant patients transplanted and not waiting on the waiting list for kidney transplantation who attended the outpatient Renal Transplantation, University Hospital of Santa Maria from January 2012 to March 2013. Held ultrasound of carotid arteries for diagnosis and quantification of carotid atherosclerosis, as well as calculation of the Framingham score using the variables collected. The prevalence of carotid plaques was 59,38% in patients undergoing renal transplantation, and 70,37% of those on the waiting list. No significant association was found between the groups regarding the presence of carotid plaques (p = 0,379) or severity (p = 0,704). The group undergoing kidney transplantation compared to patients on the waiting list was longer on dialysis (55,25 + 44,16 months vs. 28,15 + 36,50 months, p = 0,00079), had lower mean age (45,09 + 13,04 vs. 52,48 + 14,18 years, p = 0,042), fewer diabetic patients (9% vs. 52%, p = 0,00033) and lower Framingham risk score (8,72% + 7,5 vs. 16,51% + 11,97, p = 0,002). There was no significant difference between the presence of carotid plaque and the time of renal transplantation (p = 0,399) or type of immunosuppressive regimen (p = 0,939). Intermediate correlation was found (Spearman coeff = 0,47, p = 0,0065) between the degree of Framingham and severity of carotid plaque in patients undergoing renal transplantation and lack of correlation (Spearman coeff = 0,28, p = 0,152) in the group on the waiting list. In logistic regression analysis for factors associated with the presence / absence of carotid plaque, an association was found between the Framingham score and chance of carotid plaque (OR = 1,104 [1,008 to 1,210, CI OR 95%], p = 0,033). The carotid atherosclerotic disease has a high prevalence in both patients on the waiting list, as in patients already undergoing renal transplant. The traditional cardiovascular risk factors used in the Framingham score plays an important role in the development of carotid plaques.